ANALISIS KULITAS LAYANAN E-COMMERCE MENGGUNAKAN METODE E-SERVQUAL DAN ZONE OF TOLERANCE - Yudi waliyuddin; M.Afdal; Muhammad Lutfi; Mona Fronita (Jurnal Publikasi Ilmu Komputer dan Multimedia, 2023)
E-commerce is a variety of businesses that involve widespread transactions including the exchange of information via the internet network. Tokopedia is the most visited e-commerce on the web at 146 million every month. Although there are many visitors, there are many complaint comments, such as delays in delivery and so on. The purpose of this study is to analyze service quality based on 6 dimensions of e-servqual and zone of tolerance to determine the level of tolerance for services provided by Tokopedia. From the results of the analysis obtained, the gap value of the servqual dimension is negative, meaning that customers are not satisfied with the gap of -0.78, while the results of the zone of tolerance mapping are 20 attributes whose current service position is below MSA, meaning that customers are dissatisfied with the services provided.